Sport and Physical Education for Development and Peace as a Wicked Problem (Journal of Education and Development, 2025)
Wicked problems are unlike tame problems in ways that make addressing them highly challenging. Among the key, relevant differences between wicked and tame problems in the realm of sport and physical education as vehicles for fostering development and peace are: the lack of a prescriptive, agreed-upon definition to help us resolve a wicked problem; their absence of a clear end point when all agree that the problem has been resolved; their uniqueness among other wicked problems that might look similar; and, the high stakes involved for people‟s lives when we engage with a wicked problem. Those who strive to resolve wicked problems such as those identified as the United Nations Sustainable Development Goals often turn to sport and physical education as their tool. However, their path to success in both design and implementation of appropriate programs does not always feature important aspects of wicked problems on which teachers and coaches can build. This paper examines whether that misalignment is a challenge for the design and implementation of sport and physical education programs intended to promote and foster development and peace and how to take into account features of wicked problems to strengthen such programs.